2007
DOI: 10.1021/bi061436f
|View full text |Cite
|
Sign up to set email alerts
|

A Dimerization Hierarchy in the Transmembrane Domains of the HER Receptor Family

Abstract: Bitopic membrane proteins offer an opportunity for studying transmembrane domain interactions without the structural complexity inherent to multitopic integral membrane proteins. To date, only homomeric associations have been extensively studied quantitatively. Here we propose to assess the thermodynamics of heteromeric associations, which opens the way to investigating specificity and selectivity. A very interesting system of biological relevance with single transmembrane domains possibly involved in interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 48 publications
(84 reference statements)
5
68
2
Order By: Relevance
“…ErbB2 TM domain and its pathogenic mutants have been researched intensively, [13][14][15][16][17] and it is remarkable how well the structure explains the biochemical data and confirms the structural predictions. For instance, a prediction that a GxxxG-like motif would be a part of the dimer interface has been confirmed.…”
Section: Structure Of Rtk Tm Dimersmentioning
confidence: 80%
See 1 more Smart Citation
“…ErbB2 TM domain and its pathogenic mutants have been researched intensively, [13][14][15][16][17] and it is remarkable how well the structure explains the biochemical data and confirms the structural predictions. For instance, a prediction that a GxxxG-like motif would be a part of the dimer interface has been confirmed.…”
Section: Structure Of Rtk Tm Dimersmentioning
confidence: 80%
“…So far a hierarchy of dimerization strengths has been measured for the ErbB family of receptors in detergents. 15 Detergent systems, however, are not optimal for characterization of RTK TM domain interactions, 21,31,32 and thus we are looking forward to detailed characterization of homodimer and heterodimer RTK TM domain stabilities in bilayers and in E. coli membranes in the near future.…”
Section: Thermodynamics Of Rtk Tm Domain Dimerizationmentioning
confidence: 99%
“…No changes in the cluster size or frequency were detected in these constructs compared with wild-type ErbB2. In addition to the PDZ binding motif several other domains of ErbB2 have been reported to contribute to its peculiar association properties, including the transmembrane domain (13) and the sequence 966-968 in the intracellular domain (52). Although not explicitly shown to be important for the homoassociation of ErbB2 the juxtamembrane domain (53) and the kinase domain (6) of ErbB1 are known to regulate dimerization; therefore the role these regions in inducing ErbB2 homocluster formation cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although the extracellular domain of ErbB2 has failed to form crystallographic homodimers, molecular biological and fluorescence resonance energy transfer (FRET) experiments have shown that full-length ErbB2 exists in dimers or higher-order aggregates in the plasma membrane (11,12). The implication is that the transmembrane, juxtamembrane and other intracellular domains (5,13,14) act in conjunction with the membrane environment (15) to mediate the dimerization and, thereby, functional states of ErbB proteins.…”
mentioning
confidence: 99%
“…An apparent dissociation constant was calculated from the dependence of the FRET signal on the peptide concentration, whereas the detergent concentration remained constant. Details of the equations used to perform the calculations are given in Duneau et al (2007).…”
Section: Fluorescence Resonance Energy Transfer Measurementsmentioning
confidence: 99%